(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
This study aims to highlight the impact of teachers’ cultural backgrounds on the quality of the educational process. A teacher’s cultural background is a significant factor influencing classroom education, as the culture in which a teacher is raised plays a crucial role in shaping their teaching methods and interaction with students. The impact of cultural background manifests in various dimensions, including communication styles, understanding students’ diverse needs, and classroom management strategies. It also influences how teachers address cultural differences among learners and determine appropriate teaching methods that accommodate such diversity. A teacher with broad cultural awareness can deliver educational content that aligns with students’ backgrounds, fostering effective classroom interaction. Furthermore, it enhances mutual understanding and strengthens students’ ability to engage actively in the learning process.